Investigating Gamification Effect of Frequent Flyer Program on Brand Loyalty in the Aviation Industry - Singh, Balgopal (Indian Journal of Marketing, 2022)
The frequent-flyer program is a loyalty program offered by airlines, also credited as the pioneer of gamification in services. This study empirically investigated the gamification effect of frequent-flyer programs on air passengers’ brand loyalty. A conceptual model based on the gamification theory was suggested. A questionnaire-based survey method was used for data collection from domestic air passengers in India. Data were collected from 418 respondents selected using convenient purposive sampling, and 356 filled questionnaires were used for analysis. Covariance-based structural equation modeling was used for data analysis. The path analysis and mediation test supported that the FFP game-element was positively associated with the air passengers’ loyalty. The psychological and behavioral outcomes of the game element fully mediated the relationship between the game element and the loyalty of air passengers towards aviation companies. This research would be helpful to the aviation managers to plan policies for enhancing loyalty.